(untitled) (Journal of Parents and Teachers, 2014)
The author goes through tutorship from the perspective of the different statements inside the school community: principal, counsellors, tutors, teachers, students and families. After studying different focuses, he reaches to different conclusions where the importance of information, empathy and formation in the tutorship is highlighted.